Pengaruh Strategi Pembelajaran Team Quiz Terhadap Keterampilan Berbicara Di Kelas Tinggi Sekolah Dasarpengaruh Strategi Pembelajaran Team Quiz Terhadap Keterampilan Berbicara Di Kelas Tinggi Sekolah Dasar - Cucu Agustini; Iis Nurasiah; Arsyi Rizqia Amalia (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
ABSTRACT This study aims to determine the effect of team quiz learning strategies on the speaking skills of grade VI elementary school students in nonfiction text material. This type of research is quasi-experimental which is designed in the form of Nonequivalent (Pretest and Posttest) Control Group Design. The sample used is a saturated sample that is all students of class V.1 and class V.2 SDN Suryakencana CBM Sukabumi City. The instrument used was a test, the test was given at the pretest and posttest. The learning process in the experimental class uses the team quiz learning strategy while in the control class without using the team quiz learning strategy but using conventional learning strategies with the lecture method. The results of the research data analysis that has been tested for normality and homogeneity test are obtained from the posttest value. There are differences from the average value of the experimental class and the control class. The experimental class has a final average value of 77.00 and the control class students have a final average value of 67.44, so the experimental class and control class have a ratio of 9.56. This is evidenced by the results of testing the Independent Two Sample T Test showing significant results of 0,000 smaller than the significant level (0.05), meaning that there are significant differences in results between the experimental class posttest and the control class posttest. So it can be concluded that the team quiz learning strategy has an influence on the speaking skills of fifth grade elementary school students in the 2018/2019 academic year.